Formulation and Optimization of Gastro retentive Glimepiride Floating Matrix Tablets: Pharmaceutical Science-Pharmacy for Better Health - Kishore Kamere; S.V Gopalakrishna; G.V Subbareddy (International Journal of Life Science and Pharma Research, 2022)
The main objective of this research investigational studies is to formulate floating matrix tablets of glimipride by applying simplex centroid design for optimization technique and by direct compression method. The simplex Centroid configuration was drilled as an enhancement strategy by adjusting the amount of three components all the while and holding back their total concentration constant. Ingredients HPMC K15m, Kappa-carrageenan and sodium bicarbonate as X1,X2,X3 independent Variables while response variables Y1 floating lag time Y1, Percentage drug released after 1 hour Y2% and t90 time required for 90% were considered as response variable factors for formulation and optimization of total 14 formulations simplex centroid design was applied. The measures of HPMC K15M (X1), kappa-Carrageenan (X2) and sodium bicarbonate (X3) were utilized as the autonomous factors while coasting slack time (Y1), Percentage drug discharged after 1 hour(Y2) and time required for 90% (t90) were taken as the reaction factors. According to the simplex centroid configuration complete 14 formulations were formulated. Matrices were evaluated for physical parameters, in-vitro buoyancy, swelling ability and adhesion retention period. It was inferred that the blend of kappa carrageenan and HPMC K 15 M builds the adaptability in the release pattern of the drug. This examination sets up the utilization of simplex centroid structure in the advancement of coasting network tablets with least experimentation.